Da mediação à formação de leitores literários: afetos, diálogos e intencionalidade - Melo, Dianne Cristine Rodrigues de (2023)
Surveys such as Inaf (2018) and Retratos da Leitura (2021) show that 29% of Brazilians are functionally illiterate and that the number of readers in the country fell by 4.6 million between 2015 and 2019. One of the factors attributed to this scenario is the weakness of teacher training and the reading practices adopted in schools across the country. Furthermore, since literature is a human right (CANDIDO, 2011), its absence in the school environment generates social exclusion. This research therefore seeks to investigate the process of teacher training in the early grades of elementary school, considering its influence on the formation of literary readers (FREIRE, 1970/2000; STREET, 2014; KLEIMAN, 1995; BAJOUR, 2012; REYES, 2012). Its specific objectives are: (I) to reflect on my practice, as a trainer/researcher, through critical collaborative action research; (II) to investigate the training proposal for the teachers from the perspective of collaborative action and dialogical literacy practice; (III) to propose a space for dialog and critical reflection on pedagogical practice and social inequalities so that the participants can reframe literary reading practices with their students. The guiding questions are: 1) Can the training processes contribute to changes in literary reading practices in the classroom? 2) Can the training proposal for teachers influence a more collaborative and dialogical practice in the classroom? 3) Will these literary reading practices influence the maintenance or contribute to the reduction of existing inequalities in society? Supported by Thinking Aloud in Groups (PAG) (ZANOTTO, 1995), as a literacy practice in teacher training, this study also set out to build a dialogical conception (FREIRE, 1979b) that includes the subject-child actively in the teaching-learning process (LOPEZ, 2018), recognizing that the way a child learns and relates to knowledge is intrinsically linked to the influence of affections in this process. In order to reflect on language and childhood, the theoretical contributions of Vygotsky (1984-2011) and Bakhtin (2011) will be highlighted, as they emphasize language as the starting point for human and social relationships. A critical collaborative action research project (KINCHELOE, 1997) was proposed to investigate the training of a group of teachers, using an interpretivist qualitative approach (MOITA LOPES, 2006; PENNYCOOK, 1998). The data revealed that: 1. the PAG is an effective strategy for both literary reader training and teacher training, since it is a dialogical, collaborative and democratic practice that promotes reflection and autonomy among the participants; 2. the way in which the literary experience affects each teacher is fundamental for them to be able to train literary readers; 3. intentionality in working with literature contributes to the training of critical, responsive readers who are aware of their role in society